2022
DOI: 10.3389/fendo.2022.1017468
|View full text |Cite
|
Sign up to set email alerts
|

A review of the hormones involved in the endocrine dysfunctions of polycystic ovary syndrome and their interactions

Abstract: Polycystic ovary syndrome (PCOS) affects up to 20% of women but remains poorly understood. It is a heterogeneous condition with many potential comorbidities. This review offers an overview of the dysregulation of the reproductive and metabolic systems associated with PCOS. Review of the literature informed the development of a comprehensive summarizing ‘wiring’ diagram of PCOS-related features. This review provides a justification for each diagram aspect from the relevant academic literature, and explores the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 188 publications
0
12
0
Order By: Relevance
“…More recently, a large cohort study demonstrated that the risk of developing a goiter was significantly higher in women with PCOS versus women without PCOS (OR 2.0, 95% CI 1.1−3.4) ( 24 ). The incidence of goiter in that study was 1.4 patients/year in women with PCOS versus 0.7 patients/year in the control population ( 24 ) confirming the complex nature of hormonal interactions in women with PCOS ( 43 ).…”
Section: Resultsmentioning
confidence: 58%
“…More recently, a large cohort study demonstrated that the risk of developing a goiter was significantly higher in women with PCOS versus women without PCOS (OR 2.0, 95% CI 1.1−3.4) ( 24 ). The incidence of goiter in that study was 1.4 patients/year in women with PCOS versus 0.7 patients/year in the control population ( 24 ) confirming the complex nature of hormonal interactions in women with PCOS ( 43 ).…”
Section: Resultsmentioning
confidence: 58%
“… 32 Nearly all androstenedione produced in the adrenal gland is synthesised from DHEA in humans. 33 Elevated DHEAS is considered a marker for hyperactive adrenal cortex production of androgens. 32 Majority of women with PCOS are reported to have increased DHEAS levels.…”
Section: Discussionmentioning
confidence: 99%
“…Through the HPG axis, LH release is a result of pulsatile GnRH release from the hypothalamus to the pituitary. A high pulse frequency of GnRH secretion favors the release of LH while a low frequency of GnRH secretion contributes to a greater FSH release [ 21 ]. Based on these hormonal changes, determination of the LH/FSH ratio serves as a gold standard in the assessment of PCOS and is used as a marker for ovarian reserve capacity [ 22 ].…”
Section: Hormonal Changes In Patients With Pcosmentioning
confidence: 99%